Level of satisfaction in paleontology field trips in biology, at a Peruvian private university - Cosquillo, Alexia (2025)
Students’ perception about the field trips performed during biology´s undergraduate program is an important aspect to guarantee the continuous improvement of the quality of the training given by a university. The following study aims to evaluate by an interview the satisfaction level regarding paleontology field trips by the students´ of the biology program at a Peruvian private university. It was found that, throughout the 5 years of the program, students only had 1 – 2 field trips at most, even though they mostly are a population of healthy 24 years old individuals. We concluded that the studied population did not know “Cerro La Bruja” located in Ocucaje, Ica – Perú, but considered it a good field trip location.